2021
DOI: 10.1111/jar.12939
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vocational rehabilitation group intervention on motivation and occupational self‐awareness in individuals with intellectual disabilities: A single blind, randomised control study

Abstract: Background The aim of this study was to investigate the effects of a vocational rehabilitation group intervention on motivation and occupational self‐competence in individuals with intellectual disability. Methods A single‐blind, randomised controlled study design was used. The intervention group (IG) received the group‐based intervention alongside the individualised vocational rehabilitation (IVR) and the control group (CG) continued receiving only the IVR for 8 weeks. In order to assess motivation and occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The COPM is a valid measure of participation when applicable to the population and when goals are participation‐based rather than skill‐based (Imms, 2020). It has been used with people with intellectual disability for employment (Hoffman et al, 2018; Temizkan et al, 2022), cerebral palsy (Sakzewski et al, 2007), stroke (Yang et al, 2017) and acquired brain injury (Jenkinson et al, 2007). It is recommended by the PREP manual (Law et al, 2016), supports client‐centred practice and is a suggested goal‐setting tool that aligns with NDIS processes (Mathews et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The COPM is a valid measure of participation when applicable to the population and when goals are participation‐based rather than skill‐based (Imms, 2020). It has been used with people with intellectual disability for employment (Hoffman et al, 2018; Temizkan et al, 2022), cerebral palsy (Sakzewski et al, 2007), stroke (Yang et al, 2017) and acquired brain injury (Jenkinson et al, 2007). It is recommended by the PREP manual (Law et al, 2016), supports client‐centred practice and is a suggested goal‐setting tool that aligns with NDIS processes (Mathews et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…• Expand the reach of vocational rehabilitation centres, particularly in rural areas, to ensure equal access to training and support (Aydemir-Döke, & Emir-Öksüz, 2017). • Establish systematic monitoring and reporting mechanisms to assess progress and challenges in employing PwID (Temizkan et al, 2022).…”
Section: Türkiyementioning
confidence: 99%